2006
DOI: 10.1179/174963106x123205
|View full text |Cite
|
Sign up to set email alerts
|

Coastal connections, local fishing, and sustainable egg harvesting: patterns of Viking Age inland wild resource use in Mývatn district, Northern Iceland

Abstract: The 'Landscapes of Settlement Project' has carried out archaeological and paleoenvironmental research in the Lake Mývatn region of N. Iceland since 1996. Animal bone collections dating from the late 9th century to the early 13th century AD have been recovered from five sites in different ecological zones around the lake, and three of these sites provide multiple phases datable through radiocarbon, artefacts, and volcanic tephra. Modern systematic biological and geological investigations in the Mývatn district … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 26 publications
0
45
0
4
Order By: Relevance
“…Extensive excavations have shown that Hofstaöir was a large, high-status farm; Hrisheimar was a smaller farmstead involved in specialized iron working; and Gâsir a later coastal trading center. From tephrochronology and previous 14 C measurements, Hofstaöir and Hrisheimar are estimated to have been occupied between the 9th-12th centuries AD and Gâsir between the 12th-15th centuries AD (McGovern et al 2006). At each site, the MRE or FRE was calculated using 14 C measurements of multiple samples of domestic material discarded during occupation within a single, sealed archaeological midden deposit, associated with a single archaeological phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive excavations have shown that Hofstaöir was a large, high-status farm; Hrisheimar was a smaller farmstead involved in specialized iron working; and Gâsir a later coastal trading center. From tephrochronology and previous 14 C measurements, Hofstaöir and Hrisheimar are estimated to have been occupied between the 9th-12th centuries AD and Gâsir between the 12th-15th centuries AD (McGovern et al 2006). At each site, the MRE or FRE was calculated using 14 C measurements of multiple samples of domestic material discarded during occupation within a single, sealed archaeological midden deposit, associated with a single archaeological phase.…”
Section: Methodsmentioning
confidence: 99%
“…At some sites, the human bone appears older than the horse, e.g. by -200 1 4 C yr at Ytri-Neslönd (McGovern et al 2006) (see Table 1). In this example, the human burial was also stratigraphically above the landnâm tephra fall; therefore, the 1 4 C determination on the human bone collagen appeared to be too old.…”
Section: Figure 1 Location Map Showing the Positions Of Sampled Archamentioning
confidence: 99%
See 1 more Smart Citation
“…However, stratified archaeological sites document the long-term sustainable exploitation of sea birds on both Sandoy in the Faroes (9, 23) and migratory waterfowl around Lake Mývatn in Iceland (15).…”
Section: Colonization Of the Atlantic Islandsmentioning
confidence: 99%
“…Production from imported domestic animals was supplemented by extensive hunting of seals and small whales, marine and freshwater fishing, wild fowling, egg collection, and in Greenland, caribou hunting (15)(16)(17). Large archaeofauna (animal bone collections) and a growing number of stable isotope measurements on Viking age and medieval human skeletons (15,18,19) show that these wild species (especially marine fish) provided storable buffers against terrestrial pasture productivity fluctuations and stock loss, and they constituted a regular part of the normal diet across the North Atlantic. In Greenland, the role of wild resources took on a unique importance, because Norse settlers exploited the huge populations of migratory harp and hooded seals that move along the southwest coast in spring (19).…”
Section: Colonization Of the Atlantic Islandsmentioning
confidence: 99%